Developing Dependable and Secure Cloud Applications - Weber, Ingo; Nepal, Surya; Liming Zhu (IEEE internet computing, 2016)
In this article, the authors analyze the security and dependability challenges for developing dependable and secure Cloud applications. They also provide an overview of their research and development that aims to ameliorate some of the obstacles.